Telang Flower Kombucha Hand Wash Soap as a Pharmaceutical and Antibacterial Biotechnology Product isolated from Cilegon Coconut Market Vegetable Waste: Sabun Cuci Tangan Kombucha Bunga Telang Sebagai Produk Bioteknologi Farmasi dan Antibakteri yang Diisolasi dari Limbah Sayuran Pasar Kelapa Cilegon - Rezaldi, Firman; Yenny, Ratna Fitri; Maritha, Vevi; Andry, Muhammad; Pamungkas, Barolym Tri (Journal of Applied Plant Technology, 2024)
Vegetable waste that is widely distributed in the Cilegon Banten coconut market contains pathogenic bacteria including Staphylococcus aureus, Listeria monocytogenes, Salmonella thypi, and Escherichia coli. These pathogenic bacteria have the potential to cause extraordinary events (KLB), especially food poisoning. The appeal for vegetable waste managers at the Cilegon Banten coconut market to inhibit the growth of pathogenic bacteria is to adopt a clean lifestyle by diligently washing hands with antibacterial hand washing soap after disposal of widely exposed vegetable waste along with a mixture of other infectious waste. Hand washing soap with the active ingredient telang flower kombucha in this study correlated positively in inhibiting the growth of four pathogenic bacteria. Research results have proven that hand washing soap at a concentration of 40% is the best antibacterial treatment.